Analysis of Student Mode Selection Behavior at Batam International University - Antony Hermawan; Andri Irfan Rifai; Susanty Handayani (Indonesian Journal of Multidisciplinary Science, 2022)
University students in many developing countries do not experience the same mode choices in developed countries. This study implements existing influence factors of mode choice towards a university in a developing country by analyzing the characteristics of the student’s preferences in choosing the best transportation modes under different circumstances. The primary data is taken through a stated preference survey which is then analyzed using a descriptive statistics approach and findings are compared with existing studies. Firstly, commuter students show a significant interest in driving-alone mode compared to the other four mode choices. Secondly, proximity to campus proves to be influential on students’ mode choices. Thirdly, the majority of students live within their family residences, and this influence their mode choice behavior. Lastly, the results shown are correlated only with evening-period students.